A database on the stability of silver and gold nanostructures for applications in biology and biomolecular sciences. (8th November 2016) - Weerasekera, Hasitha de Alwis; Silvero, María Jazmín; Regis Correa da Silva, Daliane; Scaiano, Juan C.
Abstract : A useful library on the stability and properties of gold/silver nanomaterials with potential biological applications. Abstract : Colloidal stability of nanoparticles in biological media is an important consideration when trying to ensure reliable data interpretation of in vitro and in vivo systems. We have developed a detailed colloidal stability library of newly synthesized gold, silver and gold-core silver-shell plasmonic nanoparticles, stabilized with aspartame, glucosamine and sucralose, in various biologically relevant buffers and bacterial and mammalian cell culture media. The stabilizer selection reflects the preference for molecules that are non-toxic, inexpensive, readily available, water soluble and easy-to-replace if that is the end-user preference. An on-line resource provides detailed stability information on each of the 81 systems examined. To illustrate how to utilize this stability library, we conducted bacterial toxicity and biocompatibility experiments through the use of one specific set of nanomaterials in the presence and absence of plasmonic irradiation.